2012 Inventory of stakeholders: The agricultural statistical system in Malawi - Mapila, Mariam A.T.J. (International Food Policy Research Institute, 2013)
An inventory of the Agricultural Statistics (AgStat) sector in Malawi was carried out with the objective of gaining greater knowledge and understanding of the roles, responsibilities, and capacities of stakeholders in the AgStat sector in the country. The inventory also aimed to provide insight into the nature of partnerships, institutional linkages, and interactions between AgStat stakeholders and to better understand the key challenges, capacity constraints, and barriers of the AgStat sector.